2018
DOI: 10.15252/embr.201643879
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 protects from K‐Ras‐driven lung carcinogenesis

Abstract: The NAD-dependent deacetylase SIRT1 can be oncogenic or tumor suppressive depending on the tissue. Little is known about the role of SIRT1 in non-small cell lung carcinoma (NSCLC), one of the deadliest cancers, that is frequently associated with mutated K-RAS Therefore, we investigated the effect of SIRT1 on K-RAS-driven lung carcinogenesis. We report that SIRT1 protein levels are downregulated by oncogenic K-RAS in a MEK and PI3K-dependent manner in mouse embryo fibroblasts (MEFs), and in human lung adenocarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 84 publications
(145 reference statements)
0
18
0
Order By: Relevance
“…SIRT1 protects from K-Ras-driven lung carcinogenesis (Costa-Machado et al 2018). The abnormal expression of SIRT1 was involved in the development of non-small-cell lung cancer (Yang 2018).…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 protects from K-Ras-driven lung carcinogenesis (Costa-Machado et al 2018). The abnormal expression of SIRT1 was involved in the development of non-small-cell lung cancer (Yang 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, SIRT1 has been demonstrated to suppress KRAS-driven lung carcinogenesis by inhibiting PI3K and MEK pathways [16]. According to the TCGA and Gene Expression Omnibus (GEO) databases, we also found that SIRT1 overexpression was correlated to better prognosis in human patients with cancers that frequently carry oncogenic RAS mutations (Figure 1 and Figure S1).…”
Section: Discussionmentioning
confidence: 75%
“…This association was also observed in independent cohorts of lung and breast cancer patients ( Figure 1B,C). Considering a previous report that increased SIRT1 expression protects from KRAS-driven lung carcinogenesis [16], we further investigated RAS-dependency in the correlation between SIRT1 expression and survival rates of patients with pancreatic, colorectal, and lung cancers, which frequently carry KRAS mutation(s), particularly on glycine 12 ( Figure 1D). There were no significant differences in the survival rates between SIRT1-high and -low groups ( Figure 1E and Figure S1B), or between KRAS mutant and wild-type groups ( Figure S1C).…”
Section: Higher Expression Of Sirt1 Correlates To Better Prognosis Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in SIRT1 expression levels are frequent molecular events in human cancers 11,[19][20][21] . Recent data have shown low expression levels of SIRT1 in human colon cancer, lung cancer, and glioblastoma.…”
Section: Discussionmentioning
confidence: 99%